Penerapan Common Knowledge Construction Model Konsep Kalor untuk Meningkatkan Keterampilan Berpikir Kreatif - Sinaga, Teti Pudan Sriaraki; Nasbey, Hadi; Wibowo, Firmanul Catur (Journal of Teaching and Learning Physics, 2024)
Physics studies natural phenomena that occur around us. To understand these natural phenomena, students need to have creative thinking skills. The common knowledge construction model is a learning model that can be used to improve creative thinking skills. The aim of this research is to determine publication trends related to virtual laboratories in the last 5 years, and the number of citations for articles published from 2018 to 2023. This research method is a literature study to determine publication trends related to common knowledge construction models for improving thinking skills. students' creativity in learning physics. This research was carried out in 3 stages, namely: selecting research criteria, selecting the period and type of document, co-occurrence analysis. Overall, articles with the keyword creative thinking skills published at the end of the 2018-2023 period focus on the relationship between physics concepts and skills. The results of this research can be used as a reference for conducting further research related to the development of CKCM learning tools and the implementation of learning tools.